Observation and quantification of three-dimensional crack propagation in poly-granular graphite - Marrow, T; Mostafavi, M; McDonald, SA; Mummery, P (European Conference on Fracture, ECF, 2012)
Our observations of fracture are generally restricted to the surface of test specimens; yet the fracture process occurs within the material. X-ray computed tomography (CT) can provide valuable insights into the failure process inside the material: when X-ray CT is combined with digital volume correlation (DVC) the response to applied loads of the displacement field within the material can be measured with high precision. In this paper we study the fracture behaviour of a short-bar chevron notch specimen fabricated from polygranular nuclear graphite - a quasi-brittle material. Tomographic absorption contrast images were obtained from the specimen before and after crack propagation. The DVC-measured displacement field was used to visualise the crack, and also to measure and map its opening displacement in 3D. Three-dimensional finite element simulation of the specimen obtained the relations between crack length, opening displacement and stress intensity factor along the crack front. The experimentally calculated crack opening displacements were consistent with the FE-predicted values, and could be used to obtain the critical stress intensity factor for crack propagation.